Fracture Characteristics of B1500HS Steel Hot Blank Parts - Hou, H.L.; Li, H.P.; He, L.F. (Проблемы прочности, 2018)
Warm and hot blanking processes were developed for solving problems in piercing and trimming of press-hardened parts, some fine blank parts with comprehensive mechanical properties could be produced by hot blanking. To establish the optimum blanking processes and evaluate the effect of blanking temperature on the sheared section surface and fracture direction. Along with the fracture mechanism and microstructure of the parts, a series of hot blanking experiments for B1500HS steels were carried out at different blanking temperatures (450–800°C) and an 8% die clearance. The experimental results show that with the blanking temperature, the smooth (burnish) zone width increases, and the fracture direction becomes nearly normal. The sheared section surface of the parts mainly demonstrates ductile fracture mainly, accompanied by local brittle fracture over the blanking temperature range of 450–600°C. A ductile fracture region contains a great amount of fine equiaxed dimples over the blanking temperature range of 650–800°C, their microstructure is of complete martensite. Разработаны процессы холодной и горячей вырубки, позволяющие решить проблемы пробивки и обрезки заготовок, полученных упрочнением под давлением. Показано, что горячая вырубка позволяет получать небольшие заготовки с полным набором механических свойств для определения оптимальных режимов вырубки и оценки влияния температуры на поверхность площадки сдвига и направление разрушения. Изучены механизм разрушения и микроструктура заготовок, выполнена серия экспериментов по горячей вырубке для стали B1500HS при различных температурах (450-800°С) и 8% отношении зазора в штампе. Экспериментально доказано, что с ростом температуры вырубки увеличивается ширина гладкой зоны, а направление разрушения становится близким к вертикальному. Поверхность площадки сдвига характеризуется вязким разрушением, сопровождающимся локальным хрупким разрушением в диапазоне температур 450-600°С. Область вязкого разрушения содержит большое количество мелких равноосных лунок в диапазоне температур 650-800°С, их микроструктура полностью состоит из мартенсита.